An Exophytic Mass of the Lower Labial Mucosa: An Exophytic Mass of the Lower Labial Mucosa - Atarbashi-Moghadam, Saede; Lotfi, Ali; Ardalani, Bahram (Regeneration, Reconstruction & Restoration (Triple R), 2025)
-